Infantile Lhermitte-Duclos Disease Treated Successfully With Rapamycin. (March 2017) - Zak, Megan; Ledbetter, Mark; Maertens, Paul
Lhermitte-Duclos disease is a rare hamartomatous tumor of the cerebellum resulting from a mutation in the phosphatase and tensin homolog (PTEN) gene: it has been reported in fewer than 10 infants. Rapamycin treatment has not yet been described in Lhermitte-Duclos disease. The infant underwent shunt placement shortly after birth for aqueductal stenosis. Her clinical progression included failure to thrive, seizures, episodes of decerebrate posturing, loss of respiratory drive, and pituitary insufficiency from mass effect. The characteristic "tiger stripe" sign on imaging prompted diagnosis. Rapamycin therapy was initiated at 18 months. Within 5 months, our patient has become responsive to her surroundings and had return of spontaneous breathing. Repeat magnetic resonance imaging (MRI) reveals lack of brainstem compression or distortion of pituitary stalk. Rapamycin should be considered in cases of Lhermitte-Duclos disease where surgical removal may not be an option, as in our case where the cerebellum was entirely involved.